1998
DOI: 10.1016/s0029-7844(97)00597-8
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Dietary Soy Supplementation on Hot Flushes

Abstract: Soy protein isolate added daily to the diet substantially reduced the frequency of hot flushes in climacteric women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
171
1
12

Year Published

1999
1999
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 392 publications
(187 citation statements)
references
References 13 publications
3
171
1
12
Order By: Relevance
“…It may be that the actual dietary content was higher, as another Australian study that provided the same supplement reported much higher urinary excretion (45 µmol/day) of DAI (86) than has been reported in other feeding studies (Table 8); however, the latter study did not observe any changes in vaginal cytology. Two more recent studies did not observe changes in vaginal cytology during soy supplementation (50,87).…”
Section: Proliferation Of Uterine and Vaginal Epitheliummentioning
confidence: 90%
“…It may be that the actual dietary content was higher, as another Australian study that provided the same supplement reported much higher urinary excretion (45 µmol/day) of DAI (86) than has been reported in other feeding studies (Table 8); however, the latter study did not observe any changes in vaginal cytology. Two more recent studies did not observe changes in vaginal cytology during soy supplementation (50,87).…”
Section: Proliferation Of Uterine and Vaginal Epitheliummentioning
confidence: 90%
“…Isoflavones have weak estrogenic properties because of their structural similarity to 17␤-estradiol [10,11]. Accumulating evidence suggests beneficial influence of soy isoflavones on metabolic and gynecologic conditions in women [12][13][14]. Recent studies in postmenopausal women, further, indicate protective effects of isoflavones on lean tissue [15] and fat-free mass [16].…”
Section: Introductionmentioning
confidence: 99%
“…However, the vaginal dryness score appeared to be more improved in the isoflavone-supplemented group compared with the control diet group 104 . The trial by Albertazzi et al 105 found significantly greater reductions in hot flush frequency and severity among isoflavone users.…”
Section: Climacteric Symptomsmentioning
confidence: 99%